2012
DOI: 10.1007/s00299-011-1225-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pr-10a overexpression on the cryopreservation success of Solanum tuberosum suspension cultures

Abstract: Although many genes are supposed to be a part of plant cell tolerance mechanisms against osmotic or salt stress, their influence on tolerance towards stress during cryopreservation procedures has rarely been investigated. For instance, the overexpression of the pathogenesis-related gene 10a (pr-10a) leads to improved osmotic tolerance in a transgenic cell culture of Solanum tuberosum cv. Désirée. In this study, a cryopreservation method, consisting of osmotic pretreatment, cryoprotection with DMSO and controll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Whereas, other studies reported enhanced salt and/or osmotic tolerance due to pr-10a overexpression [3,18,19], the results in the context of pathogen attack are not that easy to interpret. In potato plants, overexpressing pr-10a did neither lead to increased resistance against Phytophthora infestans nor against potato virus X [20], whereas in the legume Medicago truncatula , silencing of PR-10 -like proteins increased the tolerance against infection with Aphanomyces euteiches [21].…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…Whereas, other studies reported enhanced salt and/or osmotic tolerance due to pr-10a overexpression [3,18,19], the results in the context of pathogen attack are not that easy to interpret. In potato plants, overexpressing pr-10a did neither lead to increased resistance against Phytophthora infestans nor against potato virus X [20], whereas in the legume Medicago truncatula , silencing of PR-10 -like proteins increased the tolerance against infection with Aphanomyces euteiches [21].…”
Section: Introductionmentioning
confidence: 72%
“…Because elevated PR-10a proteins are repeatedly found in salt and osmotically stressed entire plants, as well as cell cultures [37], a role in stress perception or signal transduction has been postulated [7]. …”
Section: Introductionmentioning
confidence: 99%
“…PR proteins participate in a wide range of cell functions, including cell wall rigidity, signal transduction, and antimicrobial activity. Overexpression of PR proteins in plants or cells increased tolerance to salt, osmotic [ 44 , 45 ], cold [ 46 ], heavy metal and pathogen stresses [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…For cryostress experiments suspended cells were taken from the logarithmic growth phase 3 days after the last transfer. The controlled-rate cooling approach based on the method of Withers and King ( Withers and King, 1980 ) was applied using the minitest system ( Heine-Dobbernack et al, 2008 ) and the protocol described by Vaas et al (2012) . Cell suspensions were pretreated for 48 h with sorbitol (final concentrations, 0, 0.3, 0.6, and 1.2 M) then incubated in 5% (v/v) DMSO for 1.5 h, cooled at rate of -0.25°C min -1 to -40°C, and finally immersed in liquid nitrogen.…”
Section: Methodsmentioning
confidence: 99%